Carpal and cubital tunnel syndromes. Issue 8 (August 2021) - Mayne, Richard; Heron, Neil
Tingling, pain and numbness in the hand can be a major cause of morbidity for many people. Adequate hand and wrist function are required for a huge variety of daily tasks, therefore disorders of the hand and wrist can have significant detrimental effects on the quality of life for affected individuals. With any upper limb issue, it is important to consider hand dominance, occupation and pastimes of the affected person. This article focuses on the optimal diagnosis and management of carpal and cubital tunnel syndromes from a primary care perspective.